Benthic nitrogen cycling in the deep ocean of the Kuroshio Extension region - Xu, Haoming; Song, Guodong; Yang, Siqi; Zhu, Ruosi; Zhang, Guiling; Liu, Sumei (Frontiers in Marine Science, 2022)
Benthic nitrogen cycling, including nitrification, N-loss, and other nitrogen transformations, plays a crucial role in the marine nitrogen budget. However, studies on benthic nitrogen cycling mainly focus on marginal seas, while attention to the deep ocean, which occupies the largest area of the seafloor, is severely lacking. In this study, we investigate the benthic nitrogen cycling in the Kuroshio Extension region (KE) of the northwest Pacific Ocean at water depths greater than 5,000 m through 15N enrichment slurry incubation and pore-water dissolved oxygen and inorganic nitrogen profiles. The slurry incubation indicates nitrification is the predominant process in benthic nitrogen cycling. The potential nitrification rates are nearly an order of magnitude higher than dissimilatory nitrate reduction. Nitrification and total N-loss flux estimated from pore-water nitrate and ammonium profiles are 6–42 and 5–30 μmol N m−2 d−1, respectively. Generally, anammox is the predominant N-loss process in KE sediment. The temperature gradient experiment indicates that the optimum temperature for anammox and denitrification is 13 and 41°C, respectively, partially explaining anammox as the dominant process for deep-ocean benthic N-loss. Both the low concentration of ammonium in pore-water and the discrepant results between anoxic incubation amended with 15NO3− and 15NH4++14NO3− suggest that ammonium is another limiting factor for benthic anammox. N-loss activity gradually declines with the distance from the Oyashio–Kuroshio transition zone. However, nitrification has the opposite trend roughly. This reveals that the sediment in KE transfers from nitrate sink to source from north to south. This trend is mainly caused by the variation of primary production and the supplement of active organic matter, which is the energy source for microbes and the potential source for ammonium through remineralization. Overall, our results highlight temperature and ammonium as two limiting factors for deep-ocean benthic N-loss and also exhibit a tight coupling relationship between pelagic primary production and the benthic nitrogen cycle in KE.